Improving depth sensitive fluorescence spectroscopy with wavefront shaping - Hsieh, Chao-Mao (2020)
Depth sensitive optical spectroscopy detects optical spectra from different layers in layered samples, revealing crucial information about the samples, for example, and the progress of epithelial cancer. In depth sensitive fluorescence measurements, multiple light scattering in tissues significantly degrades the depth sensitivity to a subsurface target layer. To address this issue, feedback based wavefront shaping led by guide stars can be used to refocus light to increase the depth sensitivity to a target layer. However, the low target to background ratio caused by multiple scattering in tissue leads to weak fluorescence measurement from the target layer inside. In this study, we demonstrate that by using feedback based wavefront shaping, we can increase the signal contribution from the target and suppress that from the background region in tissue-like scattering phantoms. After wavefront optimization, the signal from the target can increase by quite a few times. Feedback based wavefront shaping can be very useful in depth sensitive fluorescence spectroscopy for the characterization of layered structures such as epithelial tissues.